English Literature Students' Perception of Sexual Violence/Harassment in Bombshell Film: Reader-Response Criticism - Helen Christiana; Pratiwi Retnaningdyah; Ali Mustofa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Violence or sexual harassment especially against women can still be found especially in the world of work and this is due to the lack of feminist teachings in children which results in their adulthood with patriarchal thinking. This study uses English literature students as subjects and looks at their responses to the sexual harassment/violence in the movie Bombshell. This research will discuss their opinions about the movie Bombshell, their responses to gender issues in the movie, and what things shape their responses, all of which will be taken from their answers from the questionnaires distributed and interviews. From the results obtained that there are those who like and dislike the movie and some get lessons but some do not get lessons, that their response to sexual harassment/violence is also different, some agree and some disagree and so are the things that shape their response from personal experience to seeing other people. Keywords: Film, Reader-Response Criticism, Sexual Violence/Harassment, Students’ Perception